2009
DOI: 10.1007/s11748-009-0452-y
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral multiple sclerosing hemangiomas of the lung

Abstract: This report presents a case of bilateral multiple sclerosing hemangiomas of the lung in a 73-year-old woman. A computed tomography (CT) scan of the chest showed a total of three well-defined small nodules in the right and left lower lobes of the lung. Because malignant metastatic lung tumors were highly suspected, a wedge resection of the left lower lobe was performed to obtain a definitive diagnosis. Histopathologically, two tumors of the left lower lobe were composed of epithelial-like cuboidal cells coverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 9 publications
(13 reference statements)
1
23
0
1
Order By: Relevance
“…Only one patient had multiple bilateral lesions that showed stability on follow-up, even after 4 years, concordant with outcomes described in previous case reports, suggesting that multiplicity does not necessarily imply biological aggressiveness. [6][7][8] One patient was found to have nodal metastasis, in line with the 2%-4% rate previously reported. 9 We would still classify this as a benign tumor because recurrence is reported to be very rare, even amongst those with lymph node involvement, and no mortality has been reported in the literature.…”
Section: Discussionsupporting
confidence: 86%
“…Only one patient had multiple bilateral lesions that showed stability on follow-up, even after 4 years, concordant with outcomes described in previous case reports, suggesting that multiplicity does not necessarily imply biological aggressiveness. [6][7][8] One patient was found to have nodal metastasis, in line with the 2%-4% rate previously reported. 9 We would still classify this as a benign tumor because recurrence is reported to be very rare, even amongst those with lymph node involvement, and no mortality has been reported in the literature.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, PSH may be low-grade malignancy, since cases of lymph node and lung metastases have been reported. Thus, FDG PET/CT could be useful for the differential diagnosis of low-grade malignancy of PSH, particularly when the SUVmax of PSH exceeds 2.5, or when lymph node and lung metastases are displayed on PET/CT images (9)(10)(11)(12)(13)(14), which would be of great assistance in the clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies have suggested that certain benign pulmonary tumors, such as PSH, may be low-grade malignancies, since cases of lymph node and lung metastases have been reported (9)(10)(11)(12)(13)(14), or that the malignant transformation of lung benign tumors may be possible, such as the transformation of pulmonary hamartoma into adenocarcinoma, sarcoma or squamous cell carcinoma (15)(16)(17). Thus, it is also important to compare and analyze the characteristics of 18 F-FDG PET/CT in benign lung tumors and to evaluate their metabolic activities to choose the proper clinical management.…”
Section: Introductionmentioning
confidence: 99%
“…Rare cases of multiple or bilateral PSHs have been reported [3,13] whereas the tumor can be endobronchial, pleural or mediastinal [2,7]. A slight predilection for the right lung has been reported [19].…”
Section: Discussionmentioning
confidence: 99%